2015
DOI: 10.1016/j.tourman.2014.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Do tourists value different levels of cycling infrastructure?

Abstract: This paper seeks to examine how tourists value different types of cycling infrastructure using the results from intercept stated preference survey that was carried out amongst tourists in Dublin. The attributes used in the stated preference scenarios were: time, facility type, weather, and route gradient. A nested logit model was created to analyse the data. It was found that a tourist is willing to increase their cycling time by approximately 100% in order to cycle upon a fully segregated from traffic cycling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 11 publications
0
29
0
5
Order By: Relevance
“…Starting from what has already been demonstrated in terms of the links between cycle tourism and sustainability [7], the interaction between RES and tourism [11] and finally the placed-based dimension of a civic crowdfunding campaign [10], this research has shown that a proposed ecomuseum on clean energy has the potential to attract the highest level of cycle tourists, to increase the crowd of potential funders, thereby attracting the interest of the municipalities concerned, not-for profit associations and energy and tourism firms, and thus significantly increase the beneficial effects on sustainability from the economic, social and environmental points of view. The new knowledge, experience and skills created by such a project represents new and important benefits acquired by all stakeholders, which together create a complex local network with positive effects on society.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Starting from what has already been demonstrated in terms of the links between cycle tourism and sustainability [7], the interaction between RES and tourism [11] and finally the placed-based dimension of a civic crowdfunding campaign [10], this research has shown that a proposed ecomuseum on clean energy has the potential to attract the highest level of cycle tourists, to increase the crowd of potential funders, thereby attracting the interest of the municipalities concerned, not-for profit associations and energy and tourism firms, and thus significantly increase the beneficial effects on sustainability from the economic, social and environmental points of view. The new knowledge, experience and skills created by such a project represents new and important benefits acquired by all stakeholders, which together create a complex local network with positive effects on society.…”
Section: Discussionmentioning
confidence: 94%
“…As Deenihan and Caulfield [7] stated, cycle tourists value different levels of cycling infrastructure. For example, a study of cycle tourists in Dublin revealed that a cycling facility that is fully segregated from other traffic can increase the time dedicated to cycle tourism by 100%, while providing a cycle lane beside a road can increase cycling time by 40-50%.…”
Section: Evidence From the Cycle Tourism Literaturementioning
confidence: 99%
See 3 more Smart Citations